2017
DOI: 10.1101/178756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute Hepatitis E Virus infection in two geographical regions of Nigeria

Abstract: Hepatitis E virus (HEV) remains a major public health concern in resource limited regions of the world. Yet data reporting is suboptimal and surveillance system is inadequate. In Nigeria, there is dearth of information on prevalence of acute HEV infection. This study was therefore designed to describe acute HEV infection among antenatal clinic attendees and community dwellers from two geographical regions in Nigeria. Seven hundred and fifty plasma samples were tested for HEV IgM by Enzyme Linked Immunosorbent … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…To the best of our knowledge, this study is the first reported HEV single study covering four (4) states in Nigeria, hence the possible reason for the high prevalence, since HEV occurrence was found to be associated with location in the study. Some of the previously reported hepatitis E prevalence in Nigeria included 0.4% in pregnant women among Anambra and Oyo community dwellers in two different geographical regions of Nigeria, although there was 0% prevalence among other participants in the same study (Ifeorah et al, 2017).…”
Section: Discussionmentioning
confidence: 71%
“…To the best of our knowledge, this study is the first reported HEV single study covering four (4) states in Nigeria, hence the possible reason for the high prevalence, since HEV occurrence was found to be associated with location in the study. Some of the previously reported hepatitis E prevalence in Nigeria included 0.4% in pregnant women among Anambra and Oyo community dwellers in two different geographical regions of Nigeria, although there was 0% prevalence among other participants in the same study (Ifeorah et al, 2017).…”
Section: Discussionmentioning
confidence: 71%